A Checklist for Implementing Rural Pathways to Train, Develop and Support Health Workers in Low and Middle-Income Countries - O'Sullivan, Belinda; Chater, Bruce; Bingham, Amie; Wynn-Jones, John; Couper, Ian; Hegazy, Nagwa Nashat; Kumar, Raman; Lawson, Henry; Martinez-Bianchi, Viviana; Randenikumara, Sankha; Rourke, James; Strasser, Sarah; et al. (Frontiers in Medicine, 2020)
Background There is an urgent need to scale up global action on rural workforce development. This World Health Organization-sponsored research aimed to develop a Rural Pathways Checklist. Its purpose was to guide the practical implementation of rural workforce training, development and support strategies in low and middle-income countries (LMICs). It was intended for any LMICs, stakeholder, health worker, context, or health problem. Method Multi-methods involved: 1) focus group concept testing; 2) a policy analysis; 3) a scoping review of LMIC literature; 4) consultation with a global Expert Reference Group and; 5) field-testing over an 18-month period. Results The Checklist included eight actions for implementing rural pathways in LMICs: establishing community needs; policies and partners; exploring existing workers and scope; selecting health workers; education and training; working conditions for recruitment and retention; accreditation and recognition of workers; professional support/up-skilling and; monitoring and evaluation. For each action, a summary of LMICs-specific evidence and prompts was developed to stimulate reflection and learning. To support implementation, rural pathways exemplars from different WHO regions were also compiled. Field-testing showed the Checklist was fit for purpose to guide holistic planning and benchmarking of rural pathways, irrespective of LMICs, stakeholder, or health worker type. Conclusion The Rural Pathways Checklist provides an agreed global conceptual framework for the practical implementation of “grow your own” strategies in LMICs. It can be applied to scale-up activity for rural workforce training and development in LMICs, where health workers are most limited and health needs are greatest.